Nivel de estrés en el marco de la pandemia Covid-19 de los trabajadores administrativos de la Universidad Antonio Nariño, Sede Ibagué - Leyva Parra, Ingrid Liliana; Ramírez Romer, Erika Margit (Universidad Antonio Nariño, 2022)
Numerous investigations on stress have shown great interest at a global and national level, due to the negative effects it generates on the health of people and organizations. Stress is one of the main problems the world is facing. The objective of this research work is to determine the level of stress in the framework of the Covid-19 Pandemic of the administrative workers of the Antonio Nariño University, Ibagué Campus, in order to describe the importance of stress; For this, a descriptive approach was implemented methodologically, where it was possible to obtain